LANDASAN TEORI KESTABILAN SENYAWA KOMPLEKS TEKNESIUM - Muhayatun
ABSTRACT: The use of theoretical or computational methods either for studying molecular structure or predicting the formation of new compounds is increasing and becoming popular. This application is very much needed in several areas of research. Recently, the study of technetium complexes is rapidly increasing, due to the benefit of 99mTc complexes (one of Tc nuclear isomers), which are widely used for diagnostics. The main criterium in designing new 99mTc radiopharmaceuticals is the stability of 99mTc complexes, but the design parameter for the formation of stable 99mTc complexes generally are not well defined. In order to refine the design parameter for new 99mTc compounds and to improve the preparation of new stable complexes, the structure-stability relationship of Tc compound was studied. Study of the structure-stability relationship of Tc complexes based on solid angle has been done by Kung using a Solid Angle Factor Sum (SAS). The SAS is hypothesized to be related to stability. SAS has been used by several researchers either for synthesis or designing the reaction route of the Tc complex formation and predicting the geometry of complex structures. Although the advantages of the SAS were very gratifying, but the model does not have the theoretical basis which is able to explain the correlation of steric parameters to physicochemical properties of complexes especially to those connected to a complex\'s stability. To improve the SAS model, in this research the model was modified by providing a theoretical basis for SAS. Giving a basis to the SAS concept is done by adding a term to the equation of SAS and evaluating the SAS-stability correlation. The development of SAS is directed to predict the complex\'s structure geometry because its result will be used to estimate the stability of new compounds that were designed to have special characteristics. In this research, the synthesis of the ligands ethylcysteinate dimer (ESD), mercaptoasetilglysylglysylglcine (MAG3) nd its derivative have been done. The need of these radiopharmaceuticals is especially for brain and kidney imaging. The results obtained from the correlation of the SAS value to the thermodynamic stability parameters of simple complexes show the values to have a similar trend as the standard entropy (SÂ°). The entropy approximation model was created by involving some factors which are not used in Kung\'s model, such as SASempty value and arrangement distribution of ligands. In this model, the available volume of 4 n is divided into 2 parts. One part is for ligands (SASfilled) and the other is for empty space (SASempty). The ligand space and empty space are optimized in order to get an optimum entropy value. The results show that the values of the entropy approximation model have the same tendency with the experiments. Entropy optimization to the bond length (ML) has also been done to several complexes either with lone pair electrons or without lone pair electrons. The ratio between ligand radii (R) and ML in the approximation entropy model with lone pair electrons are smaller than those in the model without lone pair electrons. The calculated R from these ratios showed that their values are within the range of experimental van der Waals radii (Rvdw). The calculations of SAS value using the calculated R for more than 100 Tc complexes provide a normalized mean value of 0.8545 Â± 0,0851 and have similar curve profiles as those of Kung\'s model. The entropy value can be obtained by multiplying the natural logarithm of the a priori degeneracy of a certain distribution (CI) and the Boltzmann constant. The results of Ω and In ) of the Tc complexes have a narrow range. The calculated 1n Ω show the same tendency to the formation energy calculated by Complete Neglect of Differential Overlap, 2nd version (CNDO/2) and experimental results of ligand exchange reactions. The predictions of isomer stability in the group of Tc/Re complexes using the calculated In Ω are in accordance with the experimental results. Study of SAS for predicting structure geometry of complexes using an MA,(By model have results close to either the experimental results using X-ray diffraction or Molecular Mechanics (MM) method. From this research, the ligand synthesis methodology of ESD, MAG3 and mercaptoasetilglysylglysylglycine metil ester (MAG3OMe) was well understood, for radiopharmaceutical preparation. The results of this research are able to provide a basic concept for the SAS to explain the structure-stability relationship and to improve Kung\'s model.